The symbolism of colors in women's and men's historical costumes (Journal of the College of Basic Education, 2022)
Colors in historical costumes and for the Abbasid period raise a lot of interest in a number of color symbols. Colors were used in many aspects of Islamic civilization in clothing, architecture, and wooden and metal furniture. It was to increase the splendor of these aspects and give them high aesthetic value.